Fig. 5 in Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions ... - Kiel, Steffen; Sami, Marco; Taviani, Marco (Zenodo, 2023)
Fig. 5. Vetigastropoda Salvini-Plawen, 1980, Patellogastropoda Lindberg, 1986 and Neomphalina McLean, 1981 from the Calcari a Lucina seep deposits in northern Italy. A–G. The colloniid (Vetigastropoda) Homalopoma domeniconii Moroni, 1966. A–B. MSF 2357 from Ca' Piantè. C–D. MSF 2365 from Ca' Piantè. E–G. MSF 1216 from Le Colline. H–L. The fissurellid (Vetigastropoda) Fissurella costicillatissima Sacco, 1897, from Le Colline. H–I. Specimen with remnants of surface sculpture (MSF 1214). J–L. Internal mold showing mantle attachment scars and foramen (MSF 1213). M–N. The lottiid (Patellogastropoda) Tectura? cf. taurinensis Sacco, 1897, from Ca' Cavalmagra (MSF 1310). O–Q. The neomphaline Retiskenea? sp. from Ca' Cavalmagra. O–P. MSF 2364. Q. MSF 1312. ... : Published as part of Kiel, Steffen, Sami, Marco & Taviani, Marco, 2023, Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions, pp. 115-160 in European Journal of Taxonomy 910 on page 128, DOI: 10.5852/ejt.2023.910.2365, http://zenodo.org/record/10350702 ...